Experimental observation of charge‐shift bond in fluorite CaF2. Issue 4 (1st August 2017) - Stachowicz, Marcin; Malinska, Maura; Parafiniuk, Jan; Woźniak, Krzysztof
Abstract : F − …F − interactions in fluorite have properties associated with the recently recognized type of interaction referred to as `charge‐shift' bonding. This finding is supported by the topology of the electron localization function and the analysis of quantum theory of atoms in molecules and crystals. These interactions are attractive in character, which is additionally indicated by the topology of non‐covalent interactions based on the reduced density gradient. Abstract : On the basis of a multipole refinement of single‐crystal X‐ray diffraction data collected using an Ag source at 90 K to a resolution of 1.63 Å −1, a quantitative experimental charge density distribution has been obtained for fluorite (CaF2 ). The atoms‐in‐molecules integrated experimental charges for Ca 2+ and F − ions are +1.40 e and −0.70 e, respectively. The derived electron‐density distribution, maximum electron‐density paths, interaction lines and bond critical points along Ca 2+ …F − and F − …F − contacts revealed the character of these interactions. The Ca 2+ …F − interaction is clearly a closed shell and ionic in character. However, the F − …F − interaction has properties associated with the recently recognized type of interaction referred to as `charge‐shift' bonding. This conclusion is supported by the topology of the electron localization function and analysis of the quantum theory of atoms in molecules and crystals topological parameters. The Ca 2+ …F − bonded radii – measured as distances from the centre of the ion to the critical point – are 1.21 Å for the Ca 2+ cation and 1.15 Å for the F − anion. These values are in a good agreement with the corresponding Shannon ionic radii. The F − …F − bond path and bond critical point is also found in the CaF2 crystal structure. According to the quantum theory of atoms in molecules and crystals, this interaction is attractive in character. This is additionally supported by the topology of non‐covalent interactions based on the reduced density gradient.